A density functional theory study of the hydrogenation and reduction of the thio-spinel Fe3S4{111} surface. Issue 5 (17th January 2019) - Roldan, Alberto; de Leeuw, Nora H.
Abstract : Greigite shows promise as a reduction catalyst and it is, therefore, essential to understand its surface chemistry under reducing conditions. Abstract : The mineral greigite, Fe3 S4, shows promising electro-reduction activity, especially towards carbon dioxide conversion to small organic molecules. We have employed density functional theory calculations with correction for the long-range dispersion forces to investigate the behavior of hydrogen on the greigite{111} surface. We have studied the adsorption, diffusion, surface reduction and associative ( i.e. Volmer–Tafel mechanism) and molecular desorption of hydrogen as a function of its coverage. We found that (i) the H ad-atoms adsorb on S sites far from metallic centres in the topmost surface layer; (ii) the reduction of greigite by hydrogen is energetically unfavorable at any surface coverage; and (iii) molecular hydrogen evolution has a transition state at ∼0.5 eV above the energy of the reactants on Fe3 S4 {111}, which is very similar to the barrier found experimentally on Pt{111}. We have also determined the electrode potential under room conditions at which the H2 evolution reaction becomes energetically barrierless.